A look into 2021 phones: A quantitative survey research study on user phone customization - Kimberly Diaz; Iftikhar Alam Khan; Anmol Zubair; Zainab Aslam (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: The research in this paper aims to identify how people modify their phones, which features are most important to them, and how phone companies can use information about their customers’ demographics to identify their products to them. The overarching goal of the research is to quantify user feedback better and to investigate new avenues for advanced phone customization. Methodology: Information about the users, including information about their devices and screenshots of their lock screens and home screens, was collected using an online survey sent out privately and publicly via direct messages. Findings: At the outset, users can alter the look of their devices by tweaking eight distinct settings: wallpaper, icons, widgets, organization, group, menu bar, launcher, and everything in between. Each user has a unique background, most of which are drawings. And then 63.75% make use of widgets, 61.25% make use of groups, and 57.50% make use other forms of organization (such as filling the screen, keeping it plain, arranging the content to see the background, using negative space, and creating patterns with the elements). Similarly, the study found that men and women use different levels of customization on their phones (men are more likely to use the basic features, while women are more likely to know the advanced ones) and that people of different ages have different levels of expertise and interest in personalizing their devices. Implications/Novel Contribution: In one of the earliest studies of its kind, the authors examine how individuals alter their mobile devices to meet their specific requirements. The collected information can help others design better-individualized services. The study provides quantitative data on how users are customizing their phones, then examines potential gaps, and finally recommends a set of features that will hopefully give phone companies new and user-tailored ideas. The user’s needs must be considered from the beginning of a product’s setup to deliver effective results.